Popular culture in Indonesia [ fluid identities in post-authoritarian politics - Heryanto, Ariel (Routledge media, culture, and social change in Asia series, 2008)
This book examines popular culture in Indonesia, bringing material on Indonesia?s media and popular culture to an English readership for the first time. It includes analysis of important themes including citizenship, gender, class, age and ethnicity, showing how developments in Indonesian society more generally are inextricably linked to popular culture.